XMM-Newton survey of the Local Group galaxy <ASTROBJ>M 33</ASTROBJ> - Pietsch, W.; Misanovic, Z.; Haberl, F.; Hatzidimitriou, D.; Ehle, M.; Trinchieri, G. (2004)
In an XMM-Newton raster observation of the bright Local Group spiral galaxy <ASTROBJ>M 33</ASTROBJ> we study the population of X-ray sources (X-ray binaries, supernova remnants) down to a 0.2-4.5 keV luminosity of 1035 erg s-1 - more than a factor of 10 deeper than earlier ROSAT observations. EPIC hardness ratios and optical and radio information are used to distinguish between different source classes. The survey detects 408 sources in an area of 0.80 square degree. We correlate these newly detected sources with earlier <ASTROBJ>M 33</ASTROBJ> X-ray catalogues and information from optical, infra-red and radio wavelengths. As <ASTROBJ>M 33</ASTROBJ> sources we detect 21 supernova remnants (SNR) and 23 SNR candidates, 5 super-soft sources and 2 X-ray binaries (XRBs). There are 267 sources classified as hard, which may either be XRBs or Crab-like SNRs in <ASTROBJ>M 33</ASTROBJ> or background AGN. The 44 confirmed and candidate SNRs more than double the number of X-ray detected SNRs in <ASTROBJ>M 33</ASTROBJ>. 16 of these are proposed as SNR candidates from the X-ray data for the first time. On the other hand, there are several sources not connected to <ASTROBJ>M 33</ASTROBJ>: five foreground stars, 30 foreground star candidates, 12 active galactic nucleus candidates, one background galaxy and one background galaxy candidate. Extrapolating from deep field observations we would expect 175 to 210 background sources in this field. This indicates that about half of the sources detected are within <ASTROBJ>M 33</ASTROBJ>. XMM-Newton is an ESA Science Mission with instruments and contributions directly funded by ESA Member States and the USA (NASA). Full Table \ref{master} is only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/426/11
Keywords: Astrophysics; galaxies: individual: <ASTROBJ>M 33</ASTROBJ>; X-rays: galaxies